The effect of relative humidity on the polarization Mueller matrix under the oil smoke environment - Shen, Chengbiao; Zhang, Su; Fu, Qiang; Zhan, Juntong; Duan, Jin; Li, Yingchao (Frontiers in Physics, 2023)
For the variation of the polarized Mueller matrix of oil smoke particles under different relative humidity, the polarized single scattering characteristics of oil smoke particles are studied by Mie scattering theory, and the multiple scattering simulation is implemented with Monte Carlo method. Relative humidity variation is achieved by changing in mixing of the oil smoke and the water fog particles during the same dry particle filling time. Using the 36 sets of polarized Mueller matrices method, the Mueller matrix patterns of oil smoke were calculated for four conditions of 0%,10%, 40%, and 95% relative humidity, respectively. We can verify the simulation's correctness from the simulation and the experiment results. Specifically, as the relative humidity increases, the size of the Mueller matrix pattern increases, and the patterns of m22, m33, and m44 related to the depolarization characteristic change significantly. Further, the scattering depolarization coefficients of the Mueller matrix polar decomposition increase with the rising relative humidity, and the ability of depolarization is continuously enhanced. This method determines differences in relative humidity using intuitive measurements of stabilized scattering patterns, which can present a theoretical basis for the impact of environmental variation on polarization detection.